WEBSITE-BASED EDUCATIONAL MARKETING STRATEGIES TO INCREASE NEW STUDENT ADMISSIONS IN ISLAMIC BOARDING SCHOOLS - Abd Aziz Rois; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Digital transformation has revolutionized the marketing practices of Islamic educational institutions, requiring Islamic boarding schools to adopt digital platforms to expand their information reach. This comprehensive paper aims to theoretically analyze website-based marketing strategies for increasing the enrollment of new students by examining the 4Ps marketing mix framework as the foundation of the analysis. Using a descriptive qualitative method with library research, this study synthesizes academic literature, previous research findings, and digital documentation from Islamic boarding schools. The results indicate that implementing the Marketing Mix (4P) through the boarding school’s official website has successfully transformed conventional strategies into ones that are more transparent, accountable, and accessible. By highlighting the Amtsilati Method as a Unique Selling Point (Product), transparency in tuition and boarding fee structures (Price), online registration features as a virtual location (Place), and optimization of SEO and visual content (Promotion), the institution has been able to build a strong digital brand. This strategy has proven to be the primary catalyst in restoring the trend of new student enrollment, which had previously been fluctuating, with an increase of 21.9% to 350 students by 2025.